A Case of Cutaneous Nocardiosis with Involvement of the Trachea, Anterior Mediastinum and Sternum - Xiaoyun Wang; Tao Zhou; Danqi Deng; Yun Guo (Karger Publishers, 2010)
Nocardiosis is a rare infectious disease due to Nocardia infections. In this report, we present a rare case of cutaneous nocardiosis with involvement of the trachea, anterior mediastinum and sternum. The strain of Nocardia has been isolated from bacterial culture of infected tissue. 16s rRNA sequencing confirmed that it contained the Nocardia genus. The patient was successfully treated with Co-SMZ.